The Influence of Audit Tenure, Audit Switching, and Audit Delay on Audit Quality - Areta Bhanuwati Widya Praka; Fauziyah; Fitria Magdalena Suprapto (Dinasti International Journal of Economics, Finance & Accounting, 2025)
As a critical component of financial statement audits, management-prepared financial reports are subjected to thorough and objective evaluations by independent auditing entities. A high-quality audit plays a vital role in ensuring the credibility and reliability of a company’s financial disclosures. This study aims to investigate the effect of audit tenure, audit switching, and audit delay on audit quality within the consumer goods sector listed on the Indonesia Stock Exchange (IDX) during the period 2019–2023. A purposive sampling technique was employed, and data were analyzed using multiple linear regression. The results indicate that both audit tenure and audit switching significantly influence audit quality, whereas audit delay does not demonstrate a significant effect. Additionally, accounting firm size (KAP size) was found to influence audit quality as a control variable.